A genome-wide association study reveals candidate genes for the supernumerary nipple phenotype in sheep (Ovis aries) - Peng, W.-F.; Xu, S.-S.; Ren, X.; Lv, F.-H.; Xie, X.-L.; Zhao, Y.-X.; Zhang, M.; Shen, Z.-O.; Ren, Y.-L.; Gao, L.; Shen, M.; Kantanen, Juha; et al. (Wiley, 2017)
Genome-wide association studies (GWASs) have been widely applied in livestock to identify genes associated with traits of economic interest. Here, we conducted the first GWAS of the supernumerary nipple phenotype in Wadi sheep, a native Chinese sheep breed, based on Ovine Infinium HD SNP BeadChip genotypes in a total of 144 ewes (75 cases with four teats, including two normal and two supernumerary teats, and 69 control cases with two teats). We detected 63 significant SNPs at the chromosome-wise threshold. Additionally, one candidate region (chr1: 170.723–170.734 Mb) was identified by haplotype-based association tests, with one SNP (rs413490006) surrounding functional genes BBX and CD47 on chromosome 1 being commonly identified as significant by the two mentioned analyses. Moreover, Gene Ontology enrichment for the significant SNPs identified by the GWAS analysis was functionally clustered into the categories of receptor activity and synaptic membrane. In addition, pathway mapping revealed four promising pathways (Wnt, oxytocin, MAPK and axon guidance) involved in the development of the supernumerary nipple phenotype. Our results provide novel and important insights into the genetic mechanisms underlying the phenotype of supernumerary nipples in mammals, including humans. These findings may be useful for future breeding and genetics in sheep and other livestock.
Keywords: breast cancer; genome-wide association studies; GO enrichment; pathway mapping; SNPs; Wadi sheep; Ovis aries; cartography; sheep